Association of BMI with markers of angiogenesis in healthy population - Jaswal, Shivani; Kaur, Harjeet; Kaur, Jasbinder; Gupta, Seema (International Journal of Advances in Medicine, 2018)
Background: Obesity is associated with an increased risk of atherosclerosis, which can be mediated by an increase in angiogenesis and inflammation. The objective of the present study was to explore the relationship between BMI and levels of VEGF, a circulating biomarker of angiogenesis. Methods: 225 healthy volunteers in the age group of >18 years formed the subjects of the study. Individuals with any acute or chronic illness including history of HT, DM, and smoking, alcohol or drug abuse or on any long term medication were excluded from the study. Anthropometric measurements were taken, and BMI calculated. Blood samples were taken, and serum levels of VEGF were estimated using commercially available ELISA kits. Student’s ‘t’ test was done for comparison and correlation was assessed using Pearson’s method. Results: A statistically significant difference in the levels of VEGF was found in subjects with BMI < 25 kg/m2 as compared to subjects with BMI > 25 kg/m2 (p<0.001). A significant positive correlation was found between the levels of VEGF and BMI in both males and female subjects of the study group (r=0.68 and 0.73 respectively). Conclusions: The positive correlation of levels of VEGF with BMI in the healthy subjects of the study group may be related to the expansion of adipose tissue and to the concomitant formation of new vessels to support tissue deposition. These factors may predispose an individual to an increased risk of atherosclerotic damage later in life. VEGF may therefore, have a potential as a biomarker for the prediction of cardiovascular risk and estimation may allow intervening with lifestyle modifications and nutritional changes before the disease is manifested and pharmacotherapy is required.